2016
DOI: 10.1038/npjparkd.2015.25
|View full text |Cite|
|
Sign up to set email alerts
|

Fatigue in Parkinson’s disease: report from a multidisciplinary symposium

Abstract: Fatigue is a severe problem for many people living with Parkinson's disease (PD). Best estimates suggest that more than 50% of patients experience this debilitating symptom. Little is known about its etiology or treatment, making the understanding of fatigue a true unmet need. As part of the Parkinson's Disease Foundation Community Choice Research Program, patients, caregivers, and scientists attended a symposium on fatigue on 16 and 17 October 2014. We present a summary of that meeting, reviewing what is know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
61
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 65 publications
(90 reference statements)
1
61
0
1
Order By: Relevance
“…Fatigue is generally defined as a sense of exhaustion for a defined period that is unexplained by drug effects, medical, or psychiatric disorders . Within neurological diseases, fatigue has been described as a significantly diminished energy level or an increased perception of effort disproportionate to attempted activities …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue is generally defined as a sense of exhaustion for a defined period that is unexplained by drug effects, medical, or psychiatric disorders . Within neurological diseases, fatigue has been described as a significantly diminished energy level or an increased perception of effort disproportionate to attempted activities …”
mentioning
confidence: 99%
“…The existing inconsistencies in prevalence estimates of fatigue in PD may be explained by differences in study characteristics, patient populations, and/or assessment tools employed to measure fatigue . The present systematic review and meta‐analysis aims to provide robust estimates of the prevalence of fatigue and of its clinical correlates in PD as well as to explore the extent to which specific differences in patient and/or study characteristics contribute to varying prevalence estimates.…”
mentioning
confidence: 99%
“…This underappreciated clinical problem represents one of the major complaints of patients in the daily clinical practice [Friedman et al, 2016]. This underappreciated clinical problem represents one of the major complaints of patients in the daily clinical practice [Friedman et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is a state of profound physical and/or mental weakness, associated with a feeling of abnormal and overwhelming lack of energy, distinct both qualitatively and quantitatively from general tiredness [Brown et al, 2005]. In Parkinson's disease, this is a common and disabling non-motor symptom affecting up to 70% of patients, and often related to disease progression [Alves et al, 2004;Friedman et al, 2007], however, fatigue has generally been found to be independent of disease severity [Friedman et al, 2011;Friedman et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…56 Music accompaniment in dance may help combat fatigue by activating brain areas such as the amygdala and cingulate cortex and stimulating dopamine. 48 Only one included study examined the impact of dance on fatigue.…”
mentioning
confidence: 99%